Gasification system coupled to fixed bed column aiming adsorption of H2S from biomass - Moraes, Sibéria Caroline Gomes de; Nascimento Júnior, Adalberto Freire; Santos, Shirlene Tamires Oliveira dos; Silva, Ana Maria Ribeiro Bastos da; Silva, Sérgio Peres Ramos da; Silva, Valdinete Lins; Barbosa, Celmy Maria Bezerra Menezes (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2019)
An overview of the characterization of biomass sugarcane bagasse, peanut shell and black grape peel for application of biofuels, based on laboratory tests. Initially a general explanation of the development of gasification for the production of synthetic natural gas from alternative sources, such as biomass, which can be converted from solid to gaseous fuel, passing through a process of purification through adsorption in a fixed bed system. The adsorbent was evaluated through BET, BJH, pH, humidity and ignition loss analyzes. The results of the combined gasification capacity of the adsorption column for the cleaning of the produced fuel gas and adsorption of the H2S were analyzed. The biomass results were discussed in terms of the energy potential as fuel based on the principal component analysis (PCA).